Dinamika konflik keluarga, pola asuh, dan kekerasan terhadap anak serta dampaknya terhadap perkembangan psikologis anak - Rahma, Nafilia (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the relationship between family conflict, parenting styles, and child abuse, as well as their impact on children’s psychological development. As the primary environment, the family plays a crucial role in shaping children’s emotional and social well-being; therefore, the quality of interactions within the family is critical to their psychological well-being. This study employs a qualitative approach through a literature review, examining several relevant scientific journals. The findings indicate that family conflicts that are not effectively managed can trigger emotional instability, such as anxiety and stress in children. Authoritarian and permissive parenting styles tend to have negative effects, whereas democratic parenting exerts a more positive influence on psychological development. Additionally, child abuse, whether physical or emotional, has the potential to cause trauma and long-term psychological disorders. On the other hand, open communication within the family can serve as a protective factor in mitigating these negative effects. Therefore, efforts are needed to create a harmonious and supportive family environment to optimally support children’s psychological development.